Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/ijfs.13898
|View full text |Cite
|
Sign up to set email alerts
|

Improving antioxidant activity of black bean protein by hydrolysis with protease combinations

Abstract: This study explored the use of a simplex centroid design to produce protein hydrolysates with antioxidant properties using Alcalase Ò 2.4L, Flavourzyme Ò 500L and Neutrase Ò 0.8L. Proteases kinetic parameters and the ultrafiltration of protein hydrolysates were also investigated. The highest antioxidant activity, in the studied conditions, was reached when the mixture of Alcalase Ò 2.4L and Flavourzyme Ò 500L was used in the hydrolysates production. The antioxidant power of the black bean proteins, measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Alcalase TM 2.4L is a B. licheniformis serine protease that contains subtilisin endoproteinase activity and high specificity for cleavage of aromatic amino acids (Pimentel, Alves, Harnedy, FitzGerald, & Oliveira, 2019; Waglay & Karboune, 2016). Neutrase TM 0.8L is an endoprotease that has high affinity for hydrophobic amino acids (Aguilar et al., 2019), and can promote (as well as Alcalase TM 2.4L) an increase in the number of target sites available for the Flavourzyme TM 500L action, which justifies the synergistic effect of the ternary combination of the applied proteases (Nchienzia, Morawicki, & Gadang, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alcalase TM 2.4L is a B. licheniformis serine protease that contains subtilisin endoproteinase activity and high specificity for cleavage of aromatic amino acids (Pimentel, Alves, Harnedy, FitzGerald, & Oliveira, 2019; Waglay & Karboune, 2016). Neutrase TM 0.8L is an endoprotease that has high affinity for hydrophobic amino acids (Aguilar et al., 2019), and can promote (as well as Alcalase TM 2.4L) an increase in the number of target sites available for the Flavourzyme TM 500L action, which justifies the synergistic effect of the ternary combination of the applied proteases (Nchienzia, Morawicki, & Gadang, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Aguilar et al. (2019) studied the effects of the addition of the substrate (black bean protein concentrate) to the enzyme Neutrase TM 0.8L and observed that the half‐life time of the enzyme was reduced from 100.46 to 87.74 min, which may affect the formation of bioactive peptides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that thermal treatments can cause thermoxidation of compounds, causing the degradation of antioxidant substances and a subsequent decrease in antioxidant activity (Korczek et al, 2020). In addition, black bean protein hydrolysate showed that the high-MW (>30 kDa) fraction had higher DPPH radical-scavenging activity than the small-MW (10 kDa) fraction (Aguilar et al, 2019). However, the small-size peptides of Zizyphus jujube hydrolysate showed the high activity of DPPH expressed by EC 50 0.6 and 0.5 mg mL À1 , respectively (Memarpoor-Yazdi et al, 2013).…”
Section: Effect Of Thermal Process On Antioxidant Activitiesmentioning
confidence: 99%
“…Food protein-derived peptides have been recognised as an important category of functional food materials, which exert various bioactivities and possible health-promoting impacts in human beyond their traditional nutritional values (Hern andez-Ledesma & Hsieh, 2017;Aguilar et al, 2019). Bioactive peptides could be produced by food processing processes such as fermentation, etc., from longer polypeptides or proteins.…”
mentioning
confidence: 99%